Science, technology and applications of metals in additive manufacturing - Dutta, Bhaskar (Metallurgist); Babu, Sudarsanam; Jared, Bradley (Additive manufacturing materials and technologies., 2019)
Science, Technology and Applications of Metal Additive Manufacturing provides a holistic picture of metal Additive Manufacturing (AM) that encompasses the science, technology and applications for the use of metal AM. Users will find design aspects, various metal AM technologies commercially available, a focus on merits and demerits, implications for qualification and certification, applications, cost modeling of AM, and future directions.